2018
DOI: 10.31579/2578-8965/008
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Versus Clinical Fetal Weight Estimation Accuracy

Abstract: Background: Sonographic fetal weight estimation is an important component of antenatal care. It was found to be more reliable method to establish fetal weight at term and more consistent in various period of gestations. Aim of study: to compare clinical and sonographic methods for assessment of fetal weight regarding sensitivity, specificity and accuracy. Subjects and Methods: The study recruited 100 women scheduled for delivery from ante-natal care clinic with 38 weeks or more of gestation. Fetal weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…13 El Helali et al did a study to compare sonographic and clinical methods for assessment of fetal weight regarding sensitivity, specificity and accuracy and concluded that USG assessment of fetal weight is a safe, reliable and sensitive method for fetal weight estimation. 14 C Co or rr re el la at ti io on n B Be et tw we ee en n U Ul lt tr ra as so on no og gr ra ap ph hi ic ca al ll ly y E Es st ti im ma at te ed d Pak Armed Forces Med J 2022; 72 (5): 1584…”
Section: Discussionmentioning
confidence: 99%
“…13 El Helali et al did a study to compare sonographic and clinical methods for assessment of fetal weight regarding sensitivity, specificity and accuracy and concluded that USG assessment of fetal weight is a safe, reliable and sensitive method for fetal weight estimation. 14 C Co or rr re el la at ti io on n B Be et tw we ee en n U Ul lt tr ra as so on no og gr ra ap ph hi ic ca al ll ly y E Es st ti im ma at te ed d Pak Armed Forces Med J 2022; 72 (5): 1584…”
Section: Discussionmentioning
confidence: 99%
“…Fetal risks like shoulder dystocia and birth asphyxia. Sonography is a well-established readily available imaging technique for estimating Fetal Weight (EFW) and fetal biometry to exclude and screen for fetal growth disorders 10. Many studies including this Nigerian study by Cletus Uche Eze et aI6…”
mentioning
confidence: 99%